Free Space Doppler Analysis and RCS of a Moving PEC Plate Under Physical Optics Approximation - Polat, Burak; Dasbasi, Ramazan (IEEE, 2021)
Physical Optics formulation of electromagnetic scattering by a perfect electric conductor (PEC) plate in arbitrary motion in free space is provided. The investigation starts with the derivation of equivalent electric moment of a Hertzian dipole whose radiation pattern simulates the scattering pattern of the PEC plate under arbitrary incidence. This dipole moment is integrated into the radiation fields of an ideal Hertzian dipole (with unit moment) in arbitrary motion to obtain the explicit expressions of electric and magnetic fields scattered by a moving PEC plate under arbitrary incidence. This is based on the method of directional currents introduced recently by the present authors. Doppler analysis of the signal received by a stationary observer is carried out for certain modes of motion of the PEC plate. Finally, time domain radar cross section of a plate in uniform rectilinear motion is derived.
Keywords: doppler analysis; doppler effect; electromagnetic radiation; Hertzian dipoles; Hertzian electrodynamics; moving media; radar cross section; physical optics; SCATTERING; ABSENCE; FIELDS; Engineering